International encyclopedia of dance a project of Dance Perspectives Foundation, Inc - Cohen, Selma Jeanne, 1920-2005.; Oxford eBooks; Dance Perspectives Foundation (New York ; Oxford : Oxford University Press, 2004)
In addition to historical and descriptive materials on dance music and costume, numerous entries provide coverage of methodologies, theories, criticism and the history of dance writing and publication.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ballet -- Encyclopedias; Dance -- Encyclopedias; Electronic books